(Re)vendo a formação continuada de professores que ensinam matemática quando o assunto é pensamento algébrico: limites e desafios - Silva, Danielle Abreu (Universidade Federal de São Carlos, 2022)
This dissertation, linked to the Graduate Program in Education (PPGE) of the Federal University of São Carlos (UFSCar) along the line "Education in Science and Mathematics", aims to analyze the movement of continuing education in a group of studies with collaborative characteristics, centered on the school, in relation to the development of algebraic thinking in the literacy cycle (1st to 3rd year). It takes as its object of analysis two extension activities offered by the Department of Theory and Pedagogical Practices (DTPP/UFSCar), via a University-School partnership, both related to the work with the thematic unit Algebra in the early years. The methodology, of a qualitative nature with a descriptive-analytical character, describes the experience of the analyzed group from their meetings at two different times: 2019 and 2021. The data production instruments include: 1) document analysis: collection of project reports in partnership with a public school of the state network, photographic collection and written reports resulting from the experiences that took place in 2019; 2) semi-structured interview with three teachers (1st, 2nd and 3rd year) and with the trainer teacher, coordinator of the actions undertaken; and 3) records of virtual interactions via synchronous meetings through Google Meet during the "Classes of Collective Pedagogical Work" (ATPC), which took place in 2021. The results obtained show that although continuing education, in the case studied, made considerable efforts to ensure that the group presented collaborative characteristics, since the formation of the group in 2019, it seems, given the limitations and challenges, when it comes to algebraic thinking, to have walked more in the perspective of problematizing the theme in a movement of reflection on the practice from of theoretical studies centered on the school environment, which contributed to the expansion of the didactic-pedagogical repertoire of the participants. This reality, emerging from countless challenges in the deepening of the theme, reveals a path to follow, which is not the only one, but fruitful: that of collaborative work and its reinvention, transgression and creative insubordination, characteristics that are so necessary in the remote context, for example. In view of the elements presented, a central result is located in the dimension of the professional development of teachers who teach Mathematics in reflective processes that culminated in the possibility of rethinking their actions and better organizing their work with the thematic unit "Algebra" in the early years.
Reviewing the continuing education of teachers who teach mathematics when the subject is algebraic thinking: limits and challenges
Keywords: Formação continuada; Prática pedagógica; Pensamento algébrico nos anos iniciais; Continuing training; Pedagogical practice; Algebraic thinking in the early years; CIENCIAS HUMANAS::EDUCACAO